2007
DOI: 10.1093/jb/mvm249
|View full text |Cite
|
Sign up to set email alerts
|

O-Mannosylation is Required for Degradation of the Endoplasmic Reticulum-associated Degradation Substrate Gas1*p via the Ubiquitin/Proteasome Pathway in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, protein O-mannosylation, which is executed by protein O-mannosyltransferases, is essential for a variety of biological processes as well as for conferring solubility to misfolded proteins. To determine if O-mannosylation plays an essential role in endoplasmic reticulum-associated degradation (ERAD) of misfolded proteins, we used a model misfolded protein, Gas1*p. The O-mannose content of Gas1*p, which is transferred by protein O-mannosyltransferases, was higher than that of Gas1p. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 56 publications
2
45
0
2
Order By: Relevance
“…O-linked mannosyl modification of secretory proteins in the ER is essential in yeast (Gentzsch and Tanner 1996) and required for cell wall integrity as well as normal morphogenesis (Strahl-Bolsinger et al 1999). The role of O-linked glycosylation in ER quality control processes remains unclear although investigators have reported influences of specific pmt mutations on turnover rates of misfolded glycoproteins (Harty et al 2001;Vashist et al 2001;Hirayama et al 2008;Goder and Melero 2011) and the PMT genes are upregulated by activation of the UPR (Travers et al 2000).…”
Section: Maturation Of Secretory Proteins In the Er: Protein Glycosylmentioning
confidence: 99%
“…O-linked mannosyl modification of secretory proteins in the ER is essential in yeast (Gentzsch and Tanner 1996) and required for cell wall integrity as well as normal morphogenesis (Strahl-Bolsinger et al 1999). The role of O-linked glycosylation in ER quality control processes remains unclear although investigators have reported influences of specific pmt mutations on turnover rates of misfolded glycoproteins (Harty et al 2001;Vashist et al 2001;Hirayama et al 2008;Goder and Melero 2011) and the PMT genes are upregulated by activation of the UPR (Travers et al 2000).…”
Section: Maturation Of Secretory Proteins In the Er: Protein Glycosylmentioning
confidence: 99%
“…Over the last decade, many roles have been described for fungal O-mannosylation, including in cell wall integrity, cell morphology, and the stability, sorting, and localization of proteins Hirayama et al, 2008;Lommel and Strahl, 2009). The initial O-mannosyltransferase reaction is performed by protein mannose transferases (PMTs), which are integral endoplasmic reticulum membrane proteins that add the first mannose to Ser or Thr residues of target proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The fate of misfolded proteins that have been Omannosylated is controversial. Whereas some of them seem increasingly protected from degradation, others are reported to be degraded by the cytosolic proteasome to which they are targeted by an unknown mechanism (Harty et al, 2001;Hirayama et al, 2008). Interestingly, like most ER chaperones or members of the ERAD machineries, PMTs are upregulated during ER stress by the unfolded protein response (UPR) (Travers et al, 2000).…”
mentioning
confidence: 99%